Peran Kaidah Ushuliyah: Mutlaq, Muqayyad, Mujmal, dan Mubayyan - Faathir Janwar; Affandi Harlanda Baros; Yulia Febrianti; Kurniati Kurniati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Ushul Fiqh is the science of law in Islam which studies rules, theories and sources in detail in order to produce Islamic law taken from these sources. Knowledge of the postulates of fiqh as a whole and the procedures for deriving legal conclusions from them as well as the conditions under which the conclusions are drawn. Ushul Fiqh is also a science that discusses the basic rules (principles) in understanding Islamic law from its detailed sources, namely the Al-Quran and Hadith which relate to human actions that are burdened by law (mukallaf), both regarding matters of action. everyday birth. Fiqh with all its laws is a product of Ushul Fiqh. In understanding religious texts, Ushul Fiqh scholars use various rules, including mutlaq, muqayyad, mujmal, and mubayyan. This journal discusses the important role of these four rules in the process of understanding and interpreting religious texts.